Pengaruh Penanaman Modal Dalam Negeri (PMDN), Penanaman Modal Asing (PMA), dan Indeks Daya Saing Daerah (IDSD) Terhadap Pertumbuhan Ekonomi di 34 Provinsi di Indonesia - Nugroho, Agung Eko; Canon, Syarwani; Payu, Bobby Rantow (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
Regional economic growth is an important indicator for assessing the success of economic development in Indonesia. Differences in investment levels, regional competitiveness, and human development quality across provinces have resulted in significant disparities in economic growth. This study aims to analyze the effects of Domestic Investment (PMDN), Foreign Direct Investment (FDI/PMA), and the Regional Competitiveness Index (RCI/IDSD) on economic growth in 34 provinces in Indonesia, with the Human Development Index (HDI/IPM) included as a control variable. The study employs panel data from 2022–2023 obtained from Statistics Indonesia (BPS), the Investment Coordinating Board (BKPM), and the National Research and Innovation Agency (BRIN). Panel data regression analysis is conducted using the Estimated Generalized Least Squares (EGLS) method to address heteroskedasticity across provinces. The results indicate that foreign direct investment has a positive and significant effect on economic growth, while domestic investment shows a significant negative effect. The Regional Competitiveness Index and the Human Development Index are found to have significant effects in the final EGLS model, indicating that regional competitiveness and human development play an important role in promoting regional economic growth. Simultaneously, all independent variables significantly influence economic growth. These findings suggest that regional economic growth is determined not only by the volume of investment but also by structural competitiveness and the quality of human capital. Therefore, regional development policies should focus on improving investment quality, strengthening regional competitiveness, and enhancing sustainable human development to achieve inclusive and balanced economic growth in Indonesia